Case Report: “Clipping” an Internal Carotid Artery Aneurysm With a Duplicated Middle Cerebral Artery and the Anterior Choroidal Artery Arising From the Dome - Otsuka, Nozomi; Yajima, Hirohisa; Miyawaki, Satoru; Koizumi, Satoshi; Kiyofuji, Satoshi; Hongo, Hiroki; Teranishi, Yu; Kin, Taichi; Saito, Nobuhito (Frontiers in Neurology, 2022)
Background A duplicated middle cerebral artery (DMCA) is an anatomical variant that includes duplication of the middle cerebral artery (MCA) and an anomalous vessel originating between the anterior choroidal artery (AChA) and the distal end of the internal carotid artery (ICA). Here, we present a case report of an ICA aneurysm with a DMCA and the AChA originating from the dome, which was successfully treated with clipping. Case Description In a 64-year-old man, preoperative angiography revealed an unruptured right ICA aneurysm with a maximum diameter of 4.3 mm, and fusion three-dimensional computer graphics revealed that a DMCA and the AChA originated from the dome. The aneurysm enlarged; therefore, clipping was performed. The closure of the aneurysm while preserving the patency of the DMCA and AChA was identified using intraoperative microvascular Doppler ultrasonography and indocyanine green video angiography. The postoperative course was uneventful, and no ischemic lesions were confirmed on MR imaging. Conclusion To the best of our knowledge, this is the first report of an ICA aneurysm with a DMCA and the AChA arising from the dome. In such cases, the anatomy of the DMCA and AChA should be well-characterized before treatment.